Trichomoniasis Vaginalis in Women Attending Family Planning Unit inAL-Liqa'a Hospital. - Khalil, Hatham; Al-Kuraishi, Azhar; AI-Naimi, Usama; AI-Naimi, Suhai (Iraqi Journal of Science, 2024)
The prevalence and the incidence trichomoniasis and other sexually transmittedinfections (STIs) correlated with risk factors among women attending familyplanning unit in AL-Liqa'a Hospital are determined. Two hundred and fifty (250)women complaining vaginal discharge were examined for the period from October2010 till September 2011. From each women full history was taken including age,duration of marriage, residence, occupation, previous history of vaginal dischargeand any history of STIs. Vaginal swabs tested microscopically and cultured onappropriate media. Trichomoniasis was detected in 18 (7.2%) out of 250 womenincluded in this study. STIs were estimated in 58 (23.2%) women, andtrichomoniasis represented about 31.0% of them. Forty women (69.0%), out of 58infected women were found to be infected with other than parasitic pathogens. Thehighest rate of STIs was found in age between (25-29) years (32.8%). The highestrate of infection with Trichomonas vaginalis was found at two age intervals (25-29)and (30-34) years old (27.8%). There was a significant differences in the marriageage, occupation (house wives vs. employed), and the numbers of the sexual contact /week between the STIs infected women and uninfected women, while there was nosignificant difference among women infected with T. vaginalis and those infectedwith other STIs. The effect of other factors was also discussed. FinallyTrichomonas vaginalis in women in Baghdad is one of the important STIs with ahigh prevalence.